Pleiotropic Roles of Cold Shock Domain Proteins in Plants - Sasaki, Kentaro; Imai, Ryozo (Frontiers in Plant Science, 2012)
The cold shock domain (CSD) is a nucleic acid binding domain that is widely conserved from bacteria to higher plants and animals. In Escherichia coli, cold shock proteins (CSPs) are composed solely of a CSD and function as RNA chaperones that destabilize RNA secondary structures. Cellular RNAs tend to be folded into unfavorable structures under low temperature conditions, and RNA chaperones resolve these structures, recovering functionality of the RNAs. CSP functions are associated mainly with cold adaptation, but they are also involved in other biological processes under normal growth conditions. Eukaryotic CSD proteins contain auxiliary domains in addition to the CSD and regulate many biological processes such as development and stress tolerance. In plants, it has been demonstrated that CSD proteins play essential roles in acquiring freezing tolerance. In addition, it has been suggested that some plant CSD proteins regulate embryo development, flowering time and fruit development. In this review, we summarize the pleiotropic biological functions of cold shock domain proteins in plants and discuss possible mechanisms by which plant CSD proteins regulate the functions of RNA molecules.